Pharmaceutical Oral Formulation of Methionine as a Pediatric Treatment in Inherited Metabolic Disease - Benjamin Querin; Arnaud Schweitzer-Chaput; Salvatore Cisternino; Sylvain Auvity; Anne-Sophie Fauqueur; Abdel Negbane; Alice Hadchouel; Joël Schlatter; Camille Cotteret (MDPI AG, 2023)
L-Methionine (Met) is an essential alpha-amino acid playing a key role in several metabolic pathways. Rare inherited metabolic diseases such as mutations affecting the MARS1 gene encoding methionine tRNA synthetase (MetRS) can cause severe lung and liver disease before the age of two years. Oral Met therapy has been shown to restore MetRS activity and improve clinical health in children. As a sulfur-containing compound, Met has a strongly unpleasant odor and taste. The objective of this study was to develop an optimized pediatric pharmaceutical formulation of Met powder, to be reconstituted with water, to obtain a stable oral suspension. Organoleptic characteristics and physicochemical stability of the powdered Met formulation and suspension were evaluated at three storage temperatures. Met quantification was assessed by a stability-indicating chromatographic method as well as microbial stability. The use of a specific fruit flavor (e.g., strawberry) with sweeteners (e.g., sucralose) was considered acceptable. No drug loss, pH changes, microbiological growth, or visual changes were observed at 23 ± 2 °C and 4 ± 2 °C with the powder formulation for 92 days, and the reconstituted suspension for at least 45 days. The developed formulation facilitates the preparation, administration, the dose adjustment and palatability of Met treatment in children.